Interplay between π-Conjugation and Exchange Magnetism in One-Dimensional Porphyrinoid Polymers - Biswas, Kalyan; Urbani, Maxence; Sánchez-Grande, Ana; Soler-Polo, Diego; Lauwaet, Koen; Matěj, Adam; Mutombo, Pingo; Veis, Libor; Brabec, Jiri; Pernal, Katarzyna; Gallego, José M; Miranda, Rodolfo; et al. (Journal of the American Chemical Society, 2022)
The synthesis of novel polymeric materials with porphyrinoid compounds as key components of the repeating units attracts widespread interest from several scientific fields in view of their extraordinary variety of functional properties with potential applications in a wide range of highly significant technologies. The vast majority of such polymers present a closed-shell ground state, and, only recently, as the result of improved synthetic strategies, the engineering of open-shell porphyrinoid polymers with spin delocalization along the conjugation length has been achieved. Here, we present a combined strategy toward the fabrication of one-dimensional porphyrinoid-based polymers homocoupled via surface-catalyzed [3 + 3] cycloaromatization of isopropyl substituents on Au(111). Scanning tunneling microscopy and noncontact atomic force microscopy describe the thermal-activated intra- and intermolecular oxidative ring closure reactions as well as the controlled tip-induced hydrogen dissociation from the porphyrinoid units. In addition, scanning tunneling spectroscopy measurements, complemented by computational investigations, reveal the open-shell character, that is, the antiferromagnetic singlet ground state (S = 0) of the formed polymers, characterized by singlet-triplet inelastic excitations observed between spins of adjacent porphyrinoid units. Our approach sheds light on the crucial relevance of the π-conjugation in the correlations between spins, while expanding the on-surface synthesis toolbox and opening avenues toward the synthesis of innovative functional nanomaterials with prospects in carbon-based spintronics.